2003
DOI: 10.1097/01.pgp.0000070849.25718.73
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gonadotropin-releasing Hormone Agonists on Uterine Volume and Vasculature and on the Immunohistochemical Expression of Basic Fibroblast Growth Factor (bFGF) in Uterine Leiomyomas

Abstract: We investigated the effect of the GnRH agonist (GnRH-a) on the uterine volume and on the immunohistochemical expression of basic fibroblast growth factor (bFGF) and the vasculature of leiomyomas. Twenty-five women were treated with leuprorelin acetate for 3 months; 46 untreated patients were enrolled as a control group. The uterine volume was measured by ultrasonography. After myomectomy or hysterectomy, the immunoexpression of bFGF and the endothelial marker, CD34, was studied and compared in treated and untr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 30 publications
1
5
0
3
Order By: Relevance
“…In contrast, GnRH antagonists induce an immediate hypoestrogenic state resulting in maximum leiomyoma reduction within 3 weeks of treatment. 13 Anastrazole induced a significant reduction of total uterine volume that is similar to that observed with GnRH agonists 14 and antagonists. 13 In contrast to …”
Section: Discussionsupporting
confidence: 66%
“…In contrast, GnRH antagonists induce an immediate hypoestrogenic state resulting in maximum leiomyoma reduction within 3 weeks of treatment. 13 Anastrazole induced a significant reduction of total uterine volume that is similar to that observed with GnRH agonists 14 and antagonists. 13 In contrast to …”
Section: Discussionsupporting
confidence: 66%
“…Growth factor signaling pathways represent a potential target for leiomyoma treatment (115). For example, Di Lieto and colleagues (116) demonstrated that reduction of uterine volume after GnRHa treatment was associated with a reduction in the expression of FGF and vascularity of leiomyomas. In addition, Ohara and colleagues (65) found that the selective progesterone receptor modulator (SPRM) asoprisnil (J867), known to inhibit proliferation and to induce apoptosis of leiomyoma cells, also decreases expression of EGF, IGF-1, TGF-β mRNA and protein.…”
Section: Role Of Individual Growth Factors In Leiomyoma Pathobiologymentioning
confidence: 99%
“…17 It significantly reduces both the uterine volume and fibroid size, intraoperative blood loss, pressure, pain, and symptoms produced by distortion of adjacent organs. 18,19 In addition to this well-known effects, several studies [13][14][15]20 support the hypothesis that GnRH-a treatment is successful in preventing adhesion formation after myomectomy.…”
Section: Discussionmentioning
confidence: 90%